2020
DOI: 10.1002/suco.201900562
|View full text |Cite
|
Sign up to set email alerts
|

The influence of casting position and disturbance induced by reinforcement on the structural concrete strength

Abstract: It is well known that control specimens used to assess the concrete strength of new structures have different casting and curing conditions than those of actual structures. Notably, after pouring of the concrete and before its hardening, a number of phenomena such as concrete bleeding and plastic settlement occur, influencing the in‐situ strength with respect to that of small and homogeneous control specimens (cubes or cylinders). In addition, the development of these phenomena and their structural implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 19 publications
1
23
0
2
Order By: Relevance
“…For vertical casting conditions (Figure 6c), these voids develop under the hoops, while they develop at a side (with respect to loading direction) of the hoop for column elements cast horizontally (Figure 6d). The presence of these voids disturb the flow of stresses and can contribute to a premature spalling of the cover, with more unfavorable conditions when the voids are located under the hoops when cast vertically 16 . It can be observed that the difference due to casting conditions is limited (7%) and smaller than that for members without reinforcement for crack control (which has been observed to be approximately 10% 16 ).…”
Section: Response Of Axially‐loaded Reinforced Concrete Columnsmentioning
confidence: 96%
See 4 more Smart Citations
“…For vertical casting conditions (Figure 6c), these voids develop under the hoops, while they develop at a side (with respect to loading direction) of the hoop for column elements cast horizontally (Figure 6d). The presence of these voids disturb the flow of stresses and can contribute to a premature spalling of the cover, with more unfavorable conditions when the voids are located under the hoops when cast vertically 16 . It can be observed that the difference due to casting conditions is limited (7%) and smaller than that for members without reinforcement for crack control (which has been observed to be approximately 10% 16 ).…”
Section: Response Of Axially‐loaded Reinforced Concrete Columnsmentioning
confidence: 96%
“…The presence of these voids disturb the flow of stresses and can contribute to a premature spalling of the cover, with more unfavorable conditions when the voids are located under the hoops when cast vertically 16 . It can be observed that the difference due to casting conditions is limited (7%) and smaller than that for members without reinforcement for crack control (which has been observed to be approximately 10% 16 ). This is associated to the fact that the disturbances due to the casting conditions are partly covered by η cc , while additional differences and those related to on‐site variability are usually accounted for in γ C for design (this topic is treated in detail in Section 5).…”
Section: Response Of Axially‐loaded Reinforced Concrete Columnsmentioning
confidence: 96%
See 3 more Smart Citations